Contexts of Altar Flowers: A Contribution to a Theology in Construction - Jokinen, Heidi (Approaching Religion, 2024)
Flowers are placed on the altar in many Christian churches. However, while many other items on the altar have given rise to a vast body of theological research, this is not the case with altar flowers. In this article the author makes a constructive contribution to the theology of altar flowers and looks at the contexts in which altar flowers are imagined and how these can help to illustrate theological elements. Two initial contexts for altar flowers are assumed: the liturgical and the extra-liturgical, suggesting that altar flowers hold particular meanings both for those who know the Christian story, and equally for those who do not. It is suggested that a role which seems merely decorative is not that after all, as deeper Christian meanings can be offered in both contexts. Moreover, altar flowers as objects of nature have the capacity to speak to new groups of people on urgent contemporary themes. Finally, it is suggested that altar flowers may also bridge a divide between the secular and sacred. Apart from contributing to the construction of a theology of altar flowers, a deeper understanding of the intersections of aesthetics, faith and reason is sought.